Chitosan-Based Coatings Incorporated with Cinnamon and Tea Extracts to Extend the Fish Fillets Shelf Life: Validation by FTIR Spectroscopy Technique. (24th August 2020) - Haghighi, Maryam; Yazdanpanah, Sedigheh
Abstract : The aim of this study was to evaluate the effect of active coatings prepared from the chitosan on the quality parameters of fish fillets. Antimicrobial and antioxidant properties were improved by addition of tea and cinnamon extracts. Different quality parameters including free fatty acids (FFA), thiobarbituric acid value (TBA), trimethylamine (TMA), total volatile basic nitrogen (TVBN), whiteness, and pH of coated and noncoated samples were evaluated during storage for 20 d at 5 ± 1°C. Moreover, FTIR characterization (i.e., wavenumber and absorbance values) was used to investigate the oxidative stability. Extracts addition to chitosan coating had noticeable influence on reducing FFA and TBA. Moreover, modified chitosan coating decreased TVBN and TMA significantly. Based on FTIR finding, control sample showed the highest oxidation value, while the treated samples with chitosan\incorporated with tea and cinnamon extracts (CTCECS) had the lowest oxidation. The results showed that FTIR technique could be successfully applied to monitor the lipid oxidation of fish fillet. Therefore, FTIR provides a fast approach to study the compositional changes of food products rather than conventional chemical analysis. The findings of our research showed that chitosan coating modified with tea and cinnamon extracts could be used as a novel active packaging to prolong the shelf life quality of fish fillet.